Elderly people on the road: an approach to a more sustainable leisure mobility - Schüttemeyer, Anke; Föbker, Stefanie; Ramatschi, Gudrun; Grotz, Reinhold (ERDKUNDE, 2004)
A sustainable development of leisure mobility has two goals: avoiding traffic and satisfying leisure needs up to old age. In this respect different living areas offer varying preconditions. Therefore, within the research project FRAME (leisure mobility of elderly people) 4,500 people aged 60 years and older, living in urban, suburban and rural regions, were questioned about their leisure activities. As expected, the results show that activities generally decrease with increasing age, but that the frequency of leisure activities does not vary significantly from living area to living area. However, clear differences between the living areas can be found when examining the type of activity and the distances covered during leisure time; suburban seniors clearly cover the longest distances. The modal split underlines these results. Additionally, long-term orientations, like the location of the former work place, influence the action space during leisure time. Spatial precondition for short leisure trips and the possibility of independent leisure activities in old age, is the proximity and quality of leisure offers. Additionally, the results of the survey show that leisure facilities spreading across numerous small towns lead neither to short trips nor can this be financed. Instead, a concentration of leisure facilities with good accessibility, is recommendable. It requires the co-operation of local authorities, leisure and transportation companies. However, a concentration must not lead to an exclusion of immobile elderly.